Sharia Mutual Funds: Protection Study For Investorsabstrak - Udzma, Linda Amala (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2023)
Mutual funds are an alternative investment because of the opportunity to get better investment returns within a certain period of time. All investments including mutual funds are inseparable from violations and crimes, so the purpose of this paper is to find out about legal protection for investors as consumers. This paper was compiled using normative research, data related to this research were obtained from literature studies, and analysis was carried out by referring to documents related to the discussion. The results of this paper show that the operational mechanism between investors and Investment Managers of Islamic mutual funds uses the wakalah and mudharabah systems. Legal Protection for Investors According to Law Number 8 of 1995 concerning Capital Markets contained in article 100 paragraph 2 and article 101 paragraph 3, Bapepam-LK has the right to carry out inspections and investigations, this is a process of supervisory activities aimed at providing protection and legal certainty for among investors. According to UUPM has the authority to give administrative sanctions and criminal sanctions. Apart from that, legal protection for investors According to Law Number 21 of 2011 concerning the Financial Services Authority in Article 28, Article 29, and Article 30, aspects of protection for capital market investors are under the authority of the OJK. Provisions related to providing information on financial products and assisting consumers in filing lawsuits in court to fulfill consumer rights.